Fibrovascular Polyp of the Esophagus in an Infant: A Rare Case Emerging from a Tribal Healthcare Setting. - Kumar, Rajan; Raj, Akanksha; Kundu, Soumi; Sheikh, Nishat Ahmed; Ansari, Md Ehtesham (Indian Journal of Child Health, 2025)
Fibrovascular polyp is a rare benign intraluminal submucosal lesion of the esophagus that usually arises from the proximal portion and, despite its non-malignant nature, can enlarge significantly and lead to life threatening complications, particularly in children where cases are exceedingly uncommon. We report a 7-month-old female infant who presented with progressive dysphagia, intermittent respiratory distress, and protrusion of a soft mass from the mouth during coughing. Imaging revealed a fat-attenuated lesion in the upper cervicothoracic esophagus, while endoscopy demonstrated a large pedunculated mass. Surgical excision was performed via left lateral pharyngo-esophagostomy, and histopathology confirmed fibrovascular polyp composed of myxoid, fibrofatty, and collagenous tissue with dilated vascular channels beneath squamous epithelium. The postoperative course was uneventful, with resolution of dysphagia and respiratory symptoms, and at three-month follow-up no recurrence was detected. This case underlines the importance of considering fibrovascular polyp in the differential diagnosis of infants presenting with unexplained dysphagia, recurrent respiratory compromise, or visible oropharyngeal masses. Although benign, delayed recognition may result in aspiration or fatal airway obstruction, making early diagnosis and prompt surgical intervention crucial. Reporting such rare pediatric cases enhances clinical awareness and contributes to timely recognition and management in future practice. Written informed parental consent was obtained for publication.